Temporal and spatial variations of the thermal growing season in China during 1961–2015. (23rd August 2017) - Cui, Linli; Shi, Jun; Ma, Yue
ABSTRACT: Based on the daily mean air temperature at 1863 meteorological stations over China from 1961 to 2015, the temporal and spatial tendencies in the growing season parameters (the start date of the growing season, GSS; the end date of the growing season, GSE; and the length of the growing season, GSL) for 0, 3, 5 and 10 °C temperature thresholds were investigated; the results showed that in the past 55 years GSL exhibited a significant extending trend at speeds of 1.5–5.0 days per 10 years in most areas of northwest China (NWC), north China (NC), northeast China (NEC) and western southwest China (SWC). The extension of GSL was attributed to an earlier GSS at a rate of 1.5–3.0 days per 10 years in most areas of NEC and NC and some parts of NWC and SWC, and a later GSE at speeds of 1.0–2.0 days per 10 years in most of NWC and northern SWC and some parts of NEC and northwestern NC. The extending trend of the GSL was prominent in northern and western China relative to southern China. The temporal variations in the regional average growing season parameters were different for four temperature thresholds and in six regions. In general, the regional GSL (GSS, GSE) was extended (advanced, delayed) continuously during 1961–2015 or had no significant trend before about 1980 and then extended (advanced, delayed) continuously. The temporal variations of the GSE were weaker than those of the GSS in most regions.